Rhodoquinone carries electrons in the mammalian electron transport chain - Valeros, Jonathan; Jerome, Madison; Tseyang, Tenzin; Vo, Paula; Do, Thang; Fajardo Palomino, Diana; Grotehans, Nils; Kunala, Manisha; Jerrett, Alexandra E; Hathiramani, Nicolai R; Mireku, Michael; Magesh, Rayna Y; et al. (Cell, 2025)
Ubiquinone (UQ), the only known electron carrier in the mammalian electron transport chain (ETC), preferentially delivers electrons to the terminal electron acceptor oxygen (O2). In hypoxia, ubiquinol (UQH2) diverts these electrons onto fumarate instead. Here, we identify rhodoquinone (RQ), an electron carrier detected in mitochondria purified from certain mouse and human tissues that preferentially delivers electrons to fumarate through the reversal of succinate dehydrogenase, independent of environmental O2 levels. The RQ/fumarate ETC is strictly present in vivo and is undetectable in cultured mammalian cells. Using genetic and pharmacologic tools that reprogram the ETC from the UQ/O2 to the RQ/fumarate pathway, we establish that these distinct ETCs support unique programs of mitochondrial function and that RQ confers protection upon hypoxia exposure in vitro and in vivo. Thus, in discovering the presence of RQ in mammals, we unveil a tractable therapeutic strategy that exploits flexibility in the ETC to ameliorate hypoxia-related conditions.
Keywords: Electrons; Mitochondria; Male; elektrony; Oxygen; ubichinon; Fumarates; Hypoxia; Succinate Dehydrogenase; transport elektronů; mužské pohlaví; sukcinátdehydrogenasa; Electron Transport; Animals; lidé; kyslík; Humans; Ubiquinone; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; fumaráty; Mice; hypoxie; mitochondrie